Organizations in depth the psychoanalysis of organizations - Gabriel, Yiannis, 1952-; Hirschhorn, Larry; Allcorn, Seth.; Sage eBooks (London : SAGE, 1999)
Illustrated with numerous examples, this is a comprehensive and systematic examination of the insights psychoanalysis can offer to the study of organisations and organisational behaviour.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Organizational behavior; Corporate culture; Psychology, Industrial; Psychoanalysis; Electronic books